Analisis Strategi Pemberdayaan Ekonomi Masyarakat Nelayan Di Kecamatan Adonara - Imelda Bengan Wua; Nikson Tameno; Fransina W. Ballo (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to determine the government's efforts to economically empower fishing communities in Adonara District and determine alternative priority aspects for the economic empowerment strategy for fishermen in Adonara District. This research uses a descriptive-qualitative approach. Data collection used was interviews, observation, and documentation. The research results show that the government's efforts to empower the fishing community's economy include optimizing fishing facilities and infrastructure, improving the quality of human resources for fishermen, and finally utilizing marine and fisheries resources. The priority alternative aspects for the economic empowerment strategy of fishing communities are economic aspects, social aspects, and environmental aspects.